Pembibitan Aren (Arenga pinnata) Unggul untuk Kontinuitas Produksi Gula Aren di Desa Jambi Tulo, Kecamatan Maro Sebo - Anggraini, Riana; Marwoto, Marwoto; Handayani, Rajjita; Hardiyanti, Rizky Ayu; Puri, Suci Ratna; Saputra, Rizky; Safitri, Mariani (Fakultas Sains dan Teknologi, Universitas Jambi, 2025)
KTH Aren Serbaguna has collaborated with the community service team in 2020 regarding training on making palm sugar, the results of the community service partners were very enthusiastic about participating in the training activities because some of the livelihoods of the residents in this village are palm sap farmers. The results of discussions with residents (farmer groups) wanted a supply of palm plants planted from superior palm seeds so that their livelihoods could continue and hopefully the production of printed palm sugar would grow. Therefore, steps need to be taken for its cultivation efforts for the sustainability of palm sugar production in the village. The solutions offered by the community service team for the partner's problems above, include: conducting counseling on understanding the characteristics of palm (Arenga pinnata), growing requirements, potential and distribution, especially how to cultivate palm by making palm nurseries, conducting training and mentoring on palm seedling techniques from parent trees and planting superior palm seeds at partner locations.